Investigating the origins of nanostructural variations in differential ethnic hair types using X‐ray scattering techniques. (26th June 2013) - Wade, M.; Tucker, I.; Cunningham, P.; Skinner, R.; Bell, F.; Lyons, T.; Patten, K.; Gonzalez, L.; Wess, T.
Synopsis Objective Human hair is a major determinant of visual ethnic differentiation. Although hair types are celebrated as part of our ethnic diversity, the approach to hair care has made the assumption that hair types are structurally and chemically similar. Although this is clearly not the case at the macroscopic level, the intervention of many hair treatments is at the nanoscopic and molecular levels. The purpose of the work presented here is to identify the main nanoscopic and molecular hierarchical differences across five different ethnic hair types from hair fibres taken exclusively from the scalp. These are Afro (subdivided into elastic 'rubber' and softer non‐elastic 'soft'), Chinese, European and Mullato (mixed race). Methods Small angle X‐Ray scattering (SAXS) is a technique capable of resolving nanostructural variations in complex materials. Individual hair fibres from different ethnic hair types were used to investigate structural features found in common and also specific to each type. Simultaneous wide angle X‐Ray scattering (WAXS) was used to analyse the submolecular level structure of the fibrous keratin present. The data sets from both techniques were analysed with principal component analysis (PCA) to identify underlying variables. Results Principal component analysis of both SAXS and WAXS data was shown to discriminate the scattering signal between different hair types. The X‐ray scattering results show a common underlying keratin intermediate filament (KIF) structure. However, distinct differences were observed in the preferential orientation and intensity signal from the lipid component of the hair. In addition, differences were observed in the intensity distribution of the very low‐angle sample‐dependent diffuse scatter surrounding the 'beamstop.' Conclusion The results indicate that the fibrous keratin scaffold remains consistent between ethnic hair types. The hierarchies made by these may be modulated by variation in the content of keratin‐associated proteins (KAPs) and lipids that alter the interfacial structures and lead to macroscopic differences in hair morphology.